Та шундыё дуннеямы: кылбуръёс / Т. Н. Чернова - Чернова Татьяна Николаевна (Удмуртия, 1986)
Экземпляры: Селтинская районная библиотека (аб) (20180707) / Инвентарный номер: 206034 / Авт.знак: Ч-45 / ГРНТИ: 17.82 / ББК: 84(2Рос.Удм)